Hydrogels in cancer treatment: mapping the future of precision drug delivery - Liu, Xiang; Zhou, Qiang; Yang, Yue; Wu, Xin; Chen, Jie; Wang, Ruoqin; Chen, Erhua (Frontiers in Immunology, 2025)
BackgroundCurrent primary tumor treatments include curative resection, chemotherapy, and radiotherapy. However, these conventional methods lack precise drug delivery. Hydrogels, adaptable to the biological characteristics of different tumors, offer potential as drug delivery systems and represent a significant area of research in tumor treatment. In this study, we aimed to conduct a bibliometric analysis to reveal the current progress and future prospects of hydrogels for drug delivery in cancer.MethodsPublications concerning hydrogels in tumor drug delivery were retrieved from the Web of Science Core Collection (WoSCC) database. Data regarding countries/regions, institutions, journals, authors, and document types were collected. Bibliometric analysis and network visualization were performed using CiteSpace, HisCite, VOSviewer, Alluvial Generator, and R software.ResultsChina, the United States, and India were the leading contributing countries. Of the 98 relevant categories, 94 experienced citation bursts between 2000 and 2024. The research team led by Professor Pourmadadi Mehrab demonstrated substantial influence in this field. The International Journal of Biological Macromolecules was the most prolific journal. The top three emergent categories originated in 2020 or later, are "Chemistry, Applied", "Engineering, Environmental", and "Biochemistry & Molecular Biology". "Designing hydrogels for controlled drug delivery" was the most highly cited article. Recent emergent keywords included immunotherapy, immunogenic cell death, carboxymethyl cellulose, and antibacterial. Key concept alluvial flow visualization revealed six terms: peritoneal carcinomatosis, iron oxide nanoparticles, drug delivery, release kinetics, carbon dots, and pathway. Nano-composite hydrogels, immunotherapy, quercetin, pancreatic cancer, and oral cancer exhibited recent activity within the cited article timeline, suggesting these areas as potential future research hotspots.ConclusionThis bibliometric analysis identifies future research directions within the developing field of hydrogels for drug delivery in cancer. This study provides recommendations and directions for the development of hydrogels as tumor drug delivery systems.